2019
DOI: 10.1177/1934578x19881549
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of Essential Oil Extracts From Panax Plants Against β-Secretase, Cholinesterase, and Amyloid Aggregation

Abstract: Numerous pharmacological studies on Panax plants have been performed. However, these studies were limited to ginsenosides, which are typical constituents in Panax plants. In our research program to discover novel agents to prevent dementia and improve dementia symptoms, especially Alzheimer’s disease (AD), we investigated the inhibitory activities of essential oil (EO) extracts from 4 Panax plants against β-secretase, amyloid β (Aβ) aggregation, acetylcholinesterase (AChE), and butyrylcholinesterase (BChE). An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Kayamoto et al [ 29 ] showed the ability of the fatty acid methyl linoleate to exert a selective activity against AChE with an IC 50 value of 68.8 μM, whereas a weak inhibitory activity was reported against BChE (IC 50 of 247.8 μM). Not active was methyl palmitate against both enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Kayamoto et al [ 29 ] showed the ability of the fatty acid methyl linoleate to exert a selective activity against AChE with an IC 50 value of 68.8 μM, whereas a weak inhibitory activity was reported against BChE (IC 50 of 247.8 μM). Not active was methyl palmitate against both enzymes.…”
Section: Resultsmentioning
confidence: 99%
“…Amyloid plaques also provoke the formation of neurofibrillary tangles of τ-protein, which along with Aβ plaques provoke the destruction of neuronal cells. Additionally, the formation of Aβ plaques leads to oxidative stress in the neurons, which accelerates the development of AD (Bui and Nguyen, 2017;Folch et al, 2016;Kawamoto et al, 2019;Kumar et al, 2015;Magalingam et al, 2018;Selkoe and Hardy, 2016).…”
Section: Description Symptoms and Pathophysiology Of Admentioning
confidence: 99%
“…The cholinergic hypothesis explains the pathophysiology of AD by a decrease of neurotransmitter ACh. It is proven that cognitive decline and memory loss are linked to the loss of cholinergic activity in the neocortex and hippocampus of AD patients brain (Bui and Nguyen, 2017;Damuka et al, 2020;Folch et al, 2016;Hampel et al, 2018;Kawamoto et al, 2019). AChE primarily degrades ACh in cholinergic synapses, while a closely related enzyme BChE has a role as a coregulator of cholinergic neurotransmission by hydrolyzing ACh.…”
Section: Description Symptoms and Pathophysiology Of Admentioning
confidence: 99%
See 2 more Smart Citations